PENGARUH SHOPPING ENJOYMENT TERHADAP IMPULSE BUYING DENGAN PRODUCT BROWSING SEBAGAI VARIABEL MEDIASI PADA KOSNUMEN SHOPEE ONLINE SHOP(STUDI PADA MAHASISWA DI UNSYIAH BANDA ACEH) - Arfianda Pratama Putra; Muhammad Adam (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to measure the effect of shopping enjoyment on impulse buying and product browsing as a mediation at consumer of Shopeee among college students of Unsyiah in Banda Aceh City. The sample used in this study is college students of Unsyiah in Banda Aceh City is totalling 270 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is simple random sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that shopping enjoyment was related to impulse buying, shopping enjoyment significantly influence product browsing, product browsing was related to impulse buying, product browsing partially mediated the relationship between shopping enjoyment and impulse buying.